2019
DOI: 10.1111/mmi.14443
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for the adaptive evolution of Geobacter sulfurreducens to perform dissimilatory iron reduction in natural environments

Abstract: The electrically conductive pili (e-pili) of Geobacter species enable extracellular electron transfer to insoluble metallic minerals, electrodes and other microbial species, which confers biogeochemical significance and global prevalence on Geobacter in diverse anaerobic environments. E-pili are constructed by truncated PilA which is considered to have evolved from full-length pilin by gene fission under positive evolutionary selection. However, this hypothesis is based on phylogenetic analysis and has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 66 publications
(136 reference statements)
1
21
0
Order By: Relevance
“…Also, construction of strains that produce an abundance of OmcS, but express synthetic pilins that yield poorly conductive pili, are defective in long-range electron transfer(18,(25)(26)29). The findings reported here, and in another recent study(30), show that deleting the gene for OmcS has no impact on the conductivity of the filaments harvested from G. sulfurreducens, further demonstrating that OmcS filaments cannot be the primary conductive protein nanowires expressed by G. sulfurreducens. Thus, the actual role of OmcS in G. sulfurreducens strain DL-1 warrants further study.Materials and MethodsBacterial strains and growth conditionsGeobacter sulfurreducens strain KN400 (20), G. metallireducens strain GS15, and the omcS strain of G. sulfurreducens DL-1 (6) were obtained from our laboratory culture collection.…”
supporting
confidence: 47%
“…Also, construction of strains that produce an abundance of OmcS, but express synthetic pilins that yield poorly conductive pili, are defective in long-range electron transfer(18,(25)(26)29). The findings reported here, and in another recent study(30), show that deleting the gene for OmcS has no impact on the conductivity of the filaments harvested from G. sulfurreducens, further demonstrating that OmcS filaments cannot be the primary conductive protein nanowires expressed by G. sulfurreducens. Thus, the actual role of OmcS in G. sulfurreducens strain DL-1 warrants further study.Materials and MethodsBacterial strains and growth conditionsGeobacter sulfurreducens strain KN400 (20), G. metallireducens strain GS15, and the omcS strain of G. sulfurreducens DL-1 (6) were obtained from our laboratory culture collection.…”
supporting
confidence: 47%
“…4, 36-52 % in transmembrane MHCs and 29-35 % in secreted MHCs). This is not surprising, as deltaproteobacterial lineages are known to reduce particulate metals through extracellular electron transfer (EET), and to conduct DIET (Leang et al, 2003;Reguera et al, 2005;Lovley, 2011;Adhikari et al, 2016). Other MHC sequences were associated with Nitrospirae, Chloroflexi, and Acidobacteria (both secreted and trans-membranal) and with Actinobacteria (secreted MHCs, Fig.…”
Section: Genomic Evidence For the Microbial Iron Reduction In Lake Kimentioning
confidence: 91%
“…Our metagenomic results suggest that Lake Kinneret microbiota may transfer electrons directly to extracellular minerals, either through multiheme c-type cytochromes or microbial nanowires, according to mechanisms described in previous reviews (Lovley, 2011;Shi et al, 2016). We investigated the trans-membranal MHCs that are anchored in either the bacterial membrane or archaeal S layer, as well as secreted MHCs.…”
Section: Genomic Evidence For the Microbial Iron Reduction In Lake Kimentioning
confidence: 92%
See 1 more Smart Citation
“…Leang et al (2010) showed that OmcS, a cytochrome that is required for Fe(III) reduction by G. sulfurreducens, was localized along the pili (Leang et al, 2010). The electrically conductive pili play a major role in the adaptation of Geobacter to perform DIR in natural environments (Liu et al, 2019). These differences in the Fe(III)-reducing mechanisms between the two species might explain their difference of affinity for Fe(III) (Liu et al, 2001;Esteve-Núñez et al, 2005) and the relative increase of Geobacter abundance, observed here in presence of goethite and hematite, with the enrichment culture that was the most efficient for Fe-oxide solubilization, i.e., culture D3.…”
Section: Geobacter and Shewanella 16s Genes Abundancesmentioning
confidence: 99%